Intraviral interactome of Chikungunya virus reveals the homo-oligomerization and palmitoylation of structural protein TF - Yin, Han (Biochem Biophys Res Commun, 2019)
Chikungunya virus (CHIKV) is a re-emerging mosquito-transmitted RNA virus causing joint and muscle pain. Although the protein-protein interactions (PPIs) between nonstructural proteins of CHIKV have been extensively established, the complete CHIKV intraviral interactome remains to be elucidated. In this study, we examined all possible CHIKV intraviral PPIs by immunoprecipitation and constructed the intraviral interactome of CHIKV. We reported 19 novel PPIs including the homo-oligomerization of TF. Disulfide bonds promoted the oligomerization of CHIKV TF protein. 2-BP, a palmitoylation inhibitor reduced the palmitoylation of TF and increased TF oligomerization. A quadruple mutant of Cys33, Cys35, Cys41, and Cys43 in TF blocked its palmitoylation and reduced oligomerization. Furthermore, we determined the association of TF with nsP1 and nsP3 in a palmitoylation-dependent manner. Construction of intraviral interactome of CHIKV provides the basis for further studying the function of CHIKV proteins.